Asymmetric pore windows in MOF membranes for natural gas valorization - Zhou, Sheng; Shekhah, Osama; Ramírez, Adrian; Lyu, Pengbo; Abou-Hamad, Edy; Jia, Jiangtao; Li, Jiantang; Bhatt, Prashant M.; Huang, Zhiyuan; Jiang, Hao; Jin, Tian; Maurin, Guillaume; et al. (Nature (London), 2022)
To use natural gas as a feedstock alternative to coal and oil, its main constituent, methane, needs to be isolated with high purity 1 . In particular, nitrogen dilutes the heating value of natural gas and is, therefore, of prime importance for removal 2 . However, the inertness of nitrogen and its similarities to methane in terms of kinetic size, polarizability and boiling point pose particular challenges for the development of energy-efficient nitrogen-removing processes 3 . Here we report a mixed-linker metal–organic framework (MOF) membrane based on fumarate ( fum ) and mesaconate ( mes ) linkers, Zr- fum 67 - mes 33 - fcu -MOF, with a pore aperture shape specific for effective nitrogen removal from natural gas. The deliberate introduction of asymmetry in the parent trefoil-shaped pore aperture induces a shape irregularity, blocking the transport of tetrahedral methane while allowing linear nitrogen to permeate. Zr- fum 67 - mes 33 - fcu -MOF membranes exhibit record-high nitrogen/methane selectivity and nitrogen permeance under practical pressures up to 50 bar, removing both carbon dioxide and nitrogen from natural gas. Techno-economic analysis shows that our membranes offer the potential to reduce methane purification costs by about 66% for nitrogen rejection and about 73% for simultaneous removal of carbon dioxide and nitrogen, relative to cryogenic distillation and amine-based carbon dioxide capture. A metal–organic framework membrane based on fumarate and mesaconate linkers is shown to have a pore aperture shape that enables efficient and cost-effective removal of nitrogen and carbon dioxide from methane.